IMPLEMENTASI METODE HYNOTEACHING DALAM MENINGKATKAN MUTU AKTIVITAS BELAJAR SISWA DI SMAN 7 DENPASAR - Arta Wiguna, Ida Bagus Alit (Jurnal Penjaminan Mutu, 2020)
The research intend to analysis and find out the application of hypnoteaching method increas of student learning activities in Hindu learning at SMAN 7 Denpasar which will be a hope in improve the quality of education. This study use qualitative research method whose research characteristic adjective in the focus of the research function to find hypotheses in certain cases or limited samples. Hypnoteacing method is part of the application of hypnotic science that can bring students to an atmosphere of relaxation in receive subject matter. The work system of hypnoteaching method is the teacher communicating to students' subconscious by change brain waves from beta to alpha. Hypnosis in learning is not a model of hypnosis that is perceived in television show hypnosis in learning is only try to build conducive and pleasant conditions in the learning process of students not made asleep. In alpha conditions, the concentration of students will be focused, when relaxed the learning process will become more meaningful. Hypnoteaching method is a learning that is suitable to be applied as the development of students' potential in modern times. It can be concluded that the implementation of hypnoteaching method at SMAN 7 Denpasar is very effective in increas student learning activity